Predominant weeds of some cereal crops in the scrub Savannah Region of Nigeria - F. B., Jafun; S. D., Abdul (Universiti Putra Malaysia Press, 2004)
A survey was conducted to determine the weed species populations inhabiting cereal farms (maize, rice and sorghum) in some parts of the scrub savannah region of Nigeria during the growing seasons of 1996-1998 with the aim of providing information for effective weed management. Sixty sites in Gubi, Miri, Inkil, Lukshi and Birshin Fulani were selected for the study. Weed samples were collected within 50cm x 50 cm quadrants and were identified using standards texts and collections of the herbarium of the Abu bakar Tafawa Belawa University, Bauchi, Nigeria. In the survey sites, 66 weed species belonging to 58 genera within 18 families were identified. Of these, 41 (62.12%) species were broad-leaves, 17 (25.76%) were grass weeds and 8 (12.12%) were sedges. The dominant weeds were Cyperus, Commelina, Kyllinga, Digitaria, Echinochloa, Imperata, Cynodon, Leucas and Chloris species. The distribution of weed species varied with crop type and site of collection.